Revision of "Aemilia" pagana species-group (Lepidoptera: Erebidae: Arctiinae), with a description of a new endemic species and comments on the conservation status - Beccacece, Hernán Mario (2018)
A taxonomical rearrangement of “Aemilia” pagana species-group is proposed: Leucanopsis pagana (Schaus in Proc Zool Soc London 1894:225–243, 1894) comb. nov. and L. ninae (Orfila in Rev..Soc. Entomol. Argent. 21:67–70, 1959) comb. nov. A new endemic species from Pampa de Achala, Córdoba, Argentina, closer to both species, is described: Leucanopsis navarroi sp. nov. These three species can be recognized because the color pattern is the darkest among species of Leucanopsis. Characteristics of male genitalia suggest the nomenclatural rearrangement proposed. Leucanopsis pagana comb. nov. has a wide distribution from the center of Brazil to northeastern Argentina, including southern Paraguay. The known distribution and geospatial analysis suggest that this species is not in danger. Leucanopsis ninae comb. nov. is restricted to only one known locality (Villa Gesell, Buenos Aires). The restricted known distribution, the different land use practices, and geospatial analysis suggest that this species could be endangered. Leucanopsis navarroi sp. nov. is endemic to the high plateau present in the center of Argentina called Pampa de Achala. The known distribution and geospatial analysis suggest that this species could be endangered. Further studies are necessary to determine effectively the conservation status of these three species.